The effect of particle size, morphology and support on the formation of palladium hydride in commercial catalysts. Issue 2 (22nd October 2018) - Parker, Stewart F.; Walker, Helen C.; Callear, Samantha K.; Grünewald, Elena; Petzold, Tina; Wolf, Dorit; Möbus, Konrad; Adam, Julian; Wieland, Stefan D.; Jiménez-Ruiz, Mónica; Albers, Peter W.
Abstract : The influence of the support on the quantity of hydrogen present in a supported palladium catalyst is characterised. The on-top hydrogen on β-PdH is observed for the first time. Abstract : The relative amounts of hydrogen retained by a range of supported palladium catalysts have been investigated by a combination of electron microscopy and spectroscopic techniques, including incoherent inelastic neutron scattering. Contrary to expectation, the hydrogen capacity is not determined solely by the metal particle size, but it is a complex interaction between the particle size and its state of aggregation. The nature of the support is not only integral to the amount of hydrogen held by the catalyst, it also causes a marked difference in the rate of release of stored hydrogen from palladium. It is more difficult to fully dehydrogenate palladium on/in the porous activated carbon than on the non-porous carbon black based catalyst. The type of support also results in differences in the form of the residual hydrogen: whether it is α- or β-hydride phase, subsurface or in the threefold surface site. Our data on the supported catalysts reinforces what has only been seen previously with palladium black and our computational study provides confirmation of the empirical assignments. We also report the first vibrational spectroscopic study of hydrogen adsorbed at the surface of β-PdH and have observed for the first time hydrogen in the on-top site. This has enabled the relative proportion of bulk- to surface-H occupation in calculated model and in industrial nanoparticles to be estimated.